1995
DOI: 10.1177/00220345950740070701
|View full text |Cite
|
Sign up to set email alerts
|

Salivary Amylase Promotes Adhesion of Oral Streptococci to Hydroxyapatite

Abstract: Recent studies have demonstrated that several species of oral streptococci, such as Streptococcus gordonii, bind soluble salivary alpha-amylase. The goal of the present study was to determine if amylase immobilized onto a surface such as hydroxyapatite can serve as an adhesion receptor for S. gordonii. Initially, human parotid saliva was fractionated on Bio-Gel P60, and fractions were screened for their ability to promote adhesion of S. gordonii to hydroxyapatite. Fractions containing alpha-amylase and proline… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
83
1
4

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(91 citation statements)
references
References 35 publications
3
83
1
4
Order By: Relevance
“…For example, while AbpA-deficient mutants adhere less well to amylase-coated hydroxyapatite and are defective in biofilm formation in vitro (Rogers et al, 2001), they colonize the teeth of rats to a greater extent than their parental strains, especially when the animals are fed a sucrose-rich diet. Although this suggests that AbpA fosters net clearance of S. gordonii in vivo, previous in vitro data did not reveal amylase agglutination of any ABS (Scannapieco et al, 1995). It is possible that other important colonization factors are unmasked or redistributed on the cell surface in AbpA-deficient strains in vivo and may serve to augment bacterial adhesion to the tooth.…”
Section: Discussionmentioning
confidence: 67%
“…For example, while AbpA-deficient mutants adhere less well to amylase-coated hydroxyapatite and are defective in biofilm formation in vitro (Rogers et al, 2001), they colonize the teeth of rats to a greater extent than their parental strains, especially when the animals are fed a sucrose-rich diet. Although this suggests that AbpA fosters net clearance of S. gordonii in vivo, previous in vitro data did not reveal amylase agglutination of any ABS (Scannapieco et al, 1995). It is possible that other important colonization factors are unmasked or redistributed on the cell surface in AbpA-deficient strains in vivo and may serve to augment bacterial adhesion to the tooth.…”
Section: Discussionmentioning
confidence: 67%
“…Hydroxylapatite (HA) can be used as a suitable in vitro model of adherence to tooth surfaces. The HA model [5] is currently the most common in vitro system in use for the study of adhesion of oral bacteria such as S. mutans [6,7]. Phosphate-buffered saline coated HA (PBS-HA) was used in the majority of our adherence assays, however, some of our adhesion experiments were carried out in the presence of saliva for comparison purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, because salivary amylase and mouth cells are components of the acquired pellicle, it could be suggested that adherence and amylase-binding are mechanisms used by S. crista for biofilm formation. As shown in other works (11,39,47), the biofilm helps cell-cell communication, which is important in the formation and development of the oral bacterial community composed by S. crista and other oral pathogens, as suggested by Xie et al (46). However, the exact role of S. crista has not been fully elucidated yet.…”
Section: Discussionmentioning
confidence: 75%
“…Streptococcus mitis, Streptococcus gordonii, Streptococcus salivarious, Streptococcus anginous, and S. crista are bacterial species that are able to bind to this amylase (9,19,37,38). Moreover, the binding-amylase capacity is related to the oral bacterial colonization ability and biofilm formation (4,16,39).…”
Section: Introductionmentioning
confidence: 99%